American Klezmer : Its Roots and Offshoots - Slobin, Mark (Book collections on Project MUSE., 2002)
The essays collected in this volume investigate American klezmer: its roots, its evolution, and its spirited revitalization. The contributors include every kind of authority on the subject and they offer a wide range of perspectives on the musical, social, and cultural history of klezmer in American life.